2008
DOI: 10.1002/app.29244
|View full text |Cite
|
Sign up to set email alerts
|

Shear behavior of flexible polyurethane foams under uniaxial compression

Abstract: The mechanisms behind the load building capabilities of a hyperbranched polymer (HBP) in polyurethane (PU) foams have been investigated, using microscopy techniques and mechanical analyses. By broadening the traditional uniaxial compression characterization of PU foams to include combined shear deformations and compression behavior, an apparent Poisson ratio of the foam could be obtained in situ. The Poisson ratio as function of uniaxial compression ratio of the foam was thus studied for foams filled with Styr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 22 publications
(41 reference statements)
2
18
0
Order By: Relevance
“…By considering the material as a 2-D isotropic plane, the Poisson's ratio [Eq. (14)] is once more shown to be controlled by the ratio between normal and tangential stiffness,…”
Section: Granular Mechanicsmentioning
confidence: 99%
“…By considering the material as a 2-D isotropic plane, the Poisson's ratio [Eq. (14)] is once more shown to be controlled by the ratio between normal and tangential stiffness,…”
Section: Granular Mechanicsmentioning
confidence: 99%
“…Figure 5 shows the dependence of compression ratio on the shear dynamic modulus. As previous research has shown [7], the shear dynamic modulus initially decreases as a function of uniaxial compression ratio, then increases at further compression. The situation was the same for the present set of materials.…”
Section: Dynamic Mechanical Characterizationmentioning
confidence: 73%
“…From our previous TEM studies of similar materials, there was no evidence of clusters of unreacted HBP in the polymeric phase of the PU foams [7]. This was the background for our further investigation of the role of the HBP in the foam.…”
Section: Ftir Characterizationmentioning
confidence: 93%
“…A support factor or sag, defined by the ratio between 65 % IFD and 25 % IFD, is one of the most important characteristics of foams because it governs comfort and durability [13]. The definition of support is the ability to hold up the weight of a person.…”
Section: (B) (A)mentioning
confidence: 99%